(3GdbUjOI GdMcejIs - (3GdHSJj, CHh GdaJM, Ydj Hf eMeO Hf GdMSjf, J(B401(3g`s
(3ChdgG (B:s
(3RjGOI GdeQA OfjGg fbUGfhQHMg ZjQ eMV GdQHM NSQGf hcd MX dG KHGJ dg (B- (3aEf eYfGg aj GdJMbjb abOGf jG YGeQ GdNQGH GdOgQ eLJgOG (B- (3HGddg gd dNQGH GdYeQ YeQGfs
(3BNQgG (B:s
(3hef Cffj CHUQJ GdbdhH Hg (B- (3SHd GdgOi hhYJ ddMb CPGf jGQH Udi Ydjg eG geQ eWQ (B- (3aCjfYJ efg ChQGb hCZUGf hGHYK Edjg SdGeG RGcjG YWQG (B- (3hGdBd GdUMH dG Jafjg CReGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 326s
(3eYLe GdeDdajf(B: 2 / 497s
(3cTa GdXfhf(B: 2 / 1336s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs